Potential Implications of a Special Safeguard Mechanism in the World Trade Organization : The Case of Wheat - Hertel, Thomas W.; Martin, Will; Leister, Amanda M. (World Bank, 2012)
The special safeguard mechanism—both quantity- and price-based—was key in the July 2008 failure to reach agreement in the World Trade Organization negotiations under the Doha Development Agenda. A stochastic simulation model of the world wheat market is used to investigate the effects of the special safeguard mechanism. As expected, the quantity-based safeguard is found to reduce imports, raise domestic prices, and boost mean domestic production in the countries that implement it. However, rather than insulating developing countries in those regions from price volatility, the quantity-based safeguard increases domestic price volatility, largely by restricting imports when domestic output is low and prices are high. The quantity-based safeguard shrinks average wheat imports nearly 50 percent in some regions, and global wheat trade falls by 4.7 percent. The price-based safeguard discriminates against lower price exporters and contributes to producer price instability.